Party control over the police (1956-1989) - Korinek, László (SIAK-Journal, 2006)
The 50 years which have passed since the struggle for freedom and the revolution of 1956 were hopefully long enough to see clear and to appreciate and understand the values of the struggle for freedom, the revolution, the news of a future of a bold struggle. If anywhere, then in the former Ministry of the Interior, things have happened which could be important experiences for the experts of police and justice. The nature of revolution is that it turns against the power institutions of the system with all its anger. The nature of a put-down revolution is that the task of punishment has to be done by policemen. If it is possible to put down a revolt with the help of a foreign power, then the police have to follow the orders of this foreignarmed power. The formula is more complex in this part of Europe. Amongst the heroes of 1956 were numerous policemen, as a part of the armed forces and amongst those policemen were also the ones who caused the wrath of the people. We have to remember the innocent victims, the mindless dying, which could be found on both sides of the barricades. 50 years ago, it was the only one year before freed Austria that helped Hungary the most. It is interesting to get to know, after the release of the secret archives, how the machinery of punishment worked.